P25 Quantitative comparison of microbubble ultrasound techniques for the assessment of hepatic fibrosis in chronic hepatitis C. (16th November 2010) - Cobbold, J; Patel, D; Cobbold, J F L; Fitzpatrick, J; Crossey, M M E; Patel, N; Thomas, H C; Taylor-Robinson, S D
Abstract : Introduction: There is increasing interest in the development of imaging-based non-invasive markers for the assessment of chronic liver disease severity. Contrast enhanced ultrasound uses microbubbles as kinetic tracers to assess liver disease severity by exploiting the intra- and extra-hepatic haemodynamic changes accompanying fibrosis and cirrhosis. Transit times of a peripherally administered microbubble bolus are reduced with increasing disease severity. Transit times have previously been calculated to include intra- and extra- hepatic components (the hepatic vein transit time, HVTT) or just the intra-hepatic component (hepatic transit time, HTT), but diagnostic accuracy has not been compared directly. Aim: The aims of this study were: 1. to compare the diagnostic accuracy of HVTT and HTT in gauging the severity of chronic hepatitis C (CHC) and 2. to assess the inter- and intra-observer reliability of the microbubble technique. Method: 75 patients with biopsy-proven CHC were studied, staged using the Ishak system. Recordings of Doppler US scans performed using the microbubble contrast agent SonoVueTM, were retrospectively analysed by two independent observers, blinded to clinical data, to determine the HVTT, defined as the time taken for the microbubble to travel from the antecubital vein to the hepatic vein, and the HTT, defined as the difference between the hepatic vein arrival time and the hepatic artery arrival time. Each patient had two recordings (with separate microbubble injections) at a 10 min interval. Diagnostic accuracy was assessed using the area under the receiver operator characteristic (AUROC) curve. Inter- and intra- observer reliability and inter-injection reliability were assessed using the intraclass correlation coefficient (ICC). Results: 35 patients had mild fibrosis (stage 0–2), 23 had moderate-to-severe fibrosis (stage 3–4) and 17 had cirrhosis (stage 5–6). The diagnostic accuracy (95% CI) of HTT and HVTT for the diagnosis of cirrhosis (stage>4) were 0.78 (0.64–0.92) and 0.71 (0.55–0.86). Diagnostic accuracy (95% CI) of HTT and HVTT for the diagnosis of fibrosis stage >2 were 0.75 (0.65–0.86) and 0.71 (0.59–0.83). Inter-observer reliability (95% CI) for HTT and HVTT were 0.92 (0.87–0.95) and 0.94 (0.91–0.97). Intra-observer reliability for HTT and HVTT were 0.98 (0.97–0.99) and 0.99 (0.98–0.99); inter-recording reliability were0.97 (0.96–0.98) and 0.97 (0.95–0.98) respectively. Conclusion: HTT is more accurate than HVTT for the diagnosis of cirrhosis and moderate-to-severe fibrosis, while the reliability both of repeated recordings and of operators' assessment of recordings was very high. HTT reflects the intra-hepatic haemodynamic changes seen in more advanced chronic liver disease accounting for shorter transit times.